Applying implementation science frameworks to understand why fisherfolk continue or discontinue pre-exposure prophylaxis for HIV prevention in Uganda: a qualitative analysis - Simon Mwima; Rhoda Kitti Wanyenze; Rose Naigino; Laura M Bogart; William Musoke; Semei C Mukama; Stella Allupo; Herbert Kadama; Barbara Mukasa (BMJ Global Health)
Introduction In Uganda, fisherfolk have an HIV prevalence between 15% and 40%, significantly higher than the national average of 5.5%. Pre-exposure prophylaxis (PrEP) is effective in preventing HIV but faces challenges in uptake and continuation among fisherfolk. This study explores factors influencing PrEP continuation and discontinuation among fisherfolk in Uganda using the Consolidated Framework for Implementation Research (CFIR).Methods Participants were recruited from two fishing communities near Entebbe, Uganda. One community received enhanced PrEP support (adherence support, educational workshops and check-in calls), while the other received standard healthcare outreach. Forty fisherfolk (20 who continued PrEP and 20 who discontinued PrEP) were interviewed 6 months after initiating PrEP. Data were analysed using directed content analysis, with high inter-rater consistency. Ethical approval and informed consent were obtained.Results Findings highlighted several determinants of PrEP continuation and discontinuation across the CFIR domains. Intervention characteristics such as side effects and the pill burden were significant barriers, particularly for women who reported nausea and stomach issues. Individual characteristics revealed that perceived HIV risk influenced PrEP use, with women’s decisions often influenced by their partners' behaviours and mobility. However, insufficient information and education, especially among women, led to misunderstandings and discontinuation. Inner-setting factors like mobility issues and the distance to healthcare clinics posed significant barriers exacerbated by the geographical isolation of fishing communities. In the outer setting, high HIV prevalence motivated PrEP initiation, but stigma, particularly the misconception that PrEP is an antiretroviral drug used by people living with HIV, led to discontinuation.Conclusion Fisherfolk in Uganda encounter multiple barriers to PrEP continuation, with women facing more significant challenges. Enhanced support strategies are essential for improving PrEP adherence and informing future HIV prevention interventions in high-risk populations.